Structural and semantic forms of verbal behavior in cross-cultural communication - Victoria V. Dobrova; Irina G. Sysueva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article the contracted forms of communication such as monorhemes as means of cross-cultural communication are analised. The given form of phrases are characterised by all the features typical to full sentences considering its structure, semantics and psychological properties. The carried empirical cross-cultural study allows to say that the use of monorhemes as the reactive contracted forms of dialogue depends on the level of language and national culture as well as individual characteristics of speakers.